2010
DOI: 10.1186/1471-2180-10-125
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa inhibits in-vitro Candida biofilm development

Abstract: BackgroundElucidation of the communal behavior of microbes in mixed species biofilms may have a major impact on understanding infectious diseases and for the therapeutics. Although, the structure and the properties of monospecies biofilms and their role in disease have been extensively studied during the last decade, the interactions within mixed biofilms consisting of bacteria and fungi such as Candida spp. have not been illustrated in depth. Hence, the aim of this study was to evaluate the interspecies inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 33 publications
(37 reference statements)
7
84
0
Order By: Relevance
“…Toxic substances are secreted by many microbial species to kill or inhibit the growth of other species. For example, P. aeruginosa is reported to kill Candida in multi-species biofilms by using virulence factors which are well characterized in human infections [53][54]. Tong et al reported that Streptococcus oligofermentans uses L-amino acid oxidase to generate hydrogen peroxide (H 2 O 2 ) from peptone and suppress the growth of S. mutans in a peptone-rich multi-species biofilms [55].…”
Section: Interactions In Multi-species Biofilmsmentioning
confidence: 99%
“…Toxic substances are secreted by many microbial species to kill or inhibit the growth of other species. For example, P. aeruginosa is reported to kill Candida in multi-species biofilms by using virulence factors which are well characterized in human infections [53][54]. Tong et al reported that Streptococcus oligofermentans uses L-amino acid oxidase to generate hydrogen peroxide (H 2 O 2 ) from peptone and suppress the growth of S. mutans in a peptone-rich multi-species biofilms [55].…”
Section: Interactions In Multi-species Biofilmsmentioning
confidence: 99%
“…aeruginosa inhibited the growth of all Candida species tested, some of the yeast species were in turn capable of inhibiting Ps. aeruginosa (Bandara et al, 2010;Treat et al, 2007). Therefore, the factors contributing to the inhibition by Ps.…”
Section: Inhibition Among Co-colonizing Cf Pathogensmentioning
confidence: 99%
“…Although the human immune system is partially responsible for controlling C. albicans infections, microbes commonly coisolated from patients suffering from such infections have been shown to produce metabolites capable of modulating C. albicans virulence (Hogan and Kolter, 2002;Morales and Hogan, 2010). As one such organism, P. aeruginosa uses a variety of physical and chemical methods to limit the growth of C. albicans (Gibson et al, 2009;Bandara et al, 2010). It attaches exclusively to the hyphal germ tubes of C. albicans and secretes several virulence factors, including 3-oxo-C12 homoserine lactone and pyocyanin, to inhibit growth of C. albicans (Hogan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%